Hepatic Adenoma - A Case Report (BIRDEM Medical Journal, 2016)
We report the case of a 32-year-old female who presented to us with incidental findings of a space occupying lesion (SOL) in liver on abdominal ultrasound (USG). She was taking oral contraceptive pill for last 9 years. Clinical examination was unremarkable and liver investigation revealed mildly raised Serum alanine aminotrasferase (ALT). Dyslipidemia was also present. Computed tomography (CT) identified a 2.5 cm lesion in the right lobe of liver at posterior aspect which was isodense. Alpha-feto protein was normal. CT guided Fine Needle Aspiration Cytology (FNAC) showed adequate cellular material containing organized reactive hepatocytes in the background of blood. No granuloma or malignant cell was seen. Findings were suggestive of hepatic adenoma.Birdem Med J 2015; 5(1) Supplement: 59-62